Why we still need the term ‘Young Carer’ - Allyn Fives; Danielle Kennan; John Canavan; Bernadine Brady (Critical Social Work, 2019)
Previous research on young carers has provided data on prevalence, the tasks performed, the impacts on the carer, and the supports they require. However, some in the disability rights movement argue that the numbers of young carers and the negative impacts of caring have been exaggerated, and that the children’s rights approach serves to undermine the rights of disabled and/or ill parents. The findings from exploratory research in Ireland suggest that it is not parental illness and/or disability that is a cause for concern, but instead levels of support to and awareness of young carers. It is argued that the term young carer should continue to be used and that services should be developed in Ireland specifically for young carers.